Pesticide mixture toxicity assessment through in situ and laboratory approaches using embryo-larval stages of the pacific oyster (Magallana gigas). (July 2021) - Kuchovská, Eliška; Gonzalez, Patrice; Bláhová, Lucie; Barré, Mathilde; Gouffier, Corentin; Cachot, Jérôme; Roméro-Ramirez, Alicia; Bláha, Luděk; Morin, Bénédicte
Abstract: Worsened state of oysters in French Arcachon Bay, demand an investigation of possible causes. This study evaluated the effects of an environmentally relevant mixture of five common pesticides on the early-life stages of the Pacific oyster ( Magallana gigas ). Laboratory assays with artificial mixture and in situ transplantation were complementarily used to investigate a series of sublethal endpoints. The laboratory exposure revealed developmental toxicity at 0.32 μg/L, which corresponds to mixture concentrations in Arcachon Bay. Downregulation of some gene transcriptions was observed at environmental level. No difference in larvae development was revealed among the three sites in Arcachon Bay. This study was the first to evaluate locomotion of oyster larvae exposed in situ . Suspected poor water quality in the inner part of Arcachon Bay was reflected by impairment at the molecular level. In conclusion, current concentrations of the tested pesticides in Arcachon Bay hinder larval development and affect several biological functions. Graphical abstract: Image 1 Highlights: 1st study to evaluate locomotion of oyster larvae exposed in situ . Pesticide mixture even at low concentration is not safe for oyster development. Water quality in Arcachon Bay is sufficient for development of well-formed larvae. Effects on the gene expression were observed at realistic concentrations. Larvae caged at sites with different pollution had variable gene expressions.